Isu dan Tantangan Evaluasi Sistem Pendidikan di Indonesia - Wahyu Sihab; Shafa Kamalia; Syaifulloh Yusuf (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2026)
This study aims to comprehensively analyze the main issues and challenges in evaluating the education system in Indonesia. This study uses a qualitative approach with a descriptiveanalytical literature review method on national education evaluation practices. The results of the study show that, first, there is a gap between policy design and implementation in the field. Second, the quality and capacity of evaluators are not yet fully adequate in carrying out authentic assessment and evaluation. Third, character education evaluation instruments are still weak and often administrative in nature. This study emphasizes that strengthening the education evaluation system in Indonesia requires a more integrative and systematic approach, including improving the capacity of evaluators, the role of teachers, the development of evaluation instruments, and government intervention through affirmative policies, such as the ADEM and Merdeka Belajar scholarship programs.